ANALISIS PERUBAHAN ANGGARAN PEMERINTAH DAERAH DALAM MENUNJANG PEMBIAYAAN PEMBANGUNAN INFRASTRUKTUR DAERAH - Ignatius Adiwidjaja; Firman Firdausi; Perdinandus . (Universitas Tribhuwana Tunggadewi, 2022)
Budget planning is a budgeting activity carried out by local governments in financing programs and activities for one fiscal year. In its implementation it is often not in accordance with the developments that have been planned so that it is necessary to make changes to the budget. This study aims to analyze changes in budget planning made by the Batu City local government in supporting infrastructure development financing during the Covid-19 pandemic. This study uses an exploratory qualitative approach. Data collection techniques using observation, interviews and documentation. Determination of informants using snowball sampling. Data analysis with reduction, presentation and conclusion. The validity of the data using triangulation techniques. The results of the study show that the budget planning that has been set has made changes to the budget due to the impact of the Covid-19 pandemic. This shows that the local government is quite good at managing regional finances. Realized regional infrastructure development can be seen from the absorption of infrastructure spending in 2020 (9.62%) in 2021 (35.50%). Supporting factors include the implementation of e-government which makes it easier for regional officials to coordinate and plan programs. The inhibiting factor is the impact of the pandemic so that infrastructure development is postponed, canceled or maintained.AbstrakPerencanaan anggaran merupakan kegiatan penganggaran yang dilakukan oleh pemerintah daerah dalam membiayai program dan kegiatan untuk satu tahun anggaran. Dalam pelaksanaanya sering tidak sesuai dengan perkembangan yang sudah direncanakan sehingga perlu dilakukan perubahan anggaran. Penelitian ini bertujuan untuk menganalisis perubahan perencanaan anggaran yang dilakukan oleh pemerintah daerah Kota Batu dalam menunjang pembiayaan pembangunan infrastruktur selama masa pandemi Covid-19. Penelitian ini menggunakan pendekatan kualitatif eksploratif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Penentuan informan menggunakan snowball sampling. Analisis data dengan reduksi, penyajian dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukan bahwa perencanaan anggaran yang ditetapkan telah dilakukan perubahan anggaran yang disebabkan dampak pandemi Covid-19. Ini menunjukan bahwa pemerintah daerah sudah cukup baik dalam mengelola keuangan daerah. Pembangunan infrastruktur daerah yang terealisasi dapat dilihat dari serapan belanja infrastruktur tahun 2020 (9,62%) tahun 2021 (35,50%). Faktor yang mendukung diantaranya penerapan e-government yang memudahkan perangkat daerah dalam berkoordinasi dan merencanakan program. Faktor yang menghambat yakni dampak pandemi sehingga pembangunan infrastruktur ditunda, dibatalkan atau dipertahankan pelaksanaanya.